Study of the knowledge attitude and practice of breastfeeding among mothers admitted in post-natal ward of Dhiraj hospital, Piparia, Vadodara - Jain, Amit; Pathak, Sunil; Rathod, Dhaval (International Journal of Contemporary Pediatrics, 2024)
Background: Objective of the study to assess the knowledge attitude and practice of breastfeeding (BF) among mothers admitted in postnatal ward of Dhiraj hospital, Piparia, Vodadara. Methods: This cross-sectional study was carried out among 340 mothers who admitted in the postnatal ward of Tertiary care hospital during January 2018 to June 2019 after approval from institutional ethics committee. Results: Total 138 mother (40.6%) had correct knowledge regarding initiation of BF within 30 min-43 (12.6%) and within 1 hour-95 (27.9%). Remaining mothers believed that BF should be started within 2 hours (169, 49.7%) or within 4 hours (33, 9.7%). In this study 214 (62.9%) mothers had adequate knowledge about positioning. Whereas 133 (39.1%) mothers had adequate knowledge about attachment. Most known sign (145, 42.6%) was “the baby’s mouth is wide open.” And least known sign (83, 24.4%) was “baby’s chin touches the breast.” The 249 (70.6%) mothers said that frequent feeding increases the quantity of breast milk secretion. 128 (37.6%) mothers said that relaxation, 138 (40.6%) mothers said that pre lacteal feed, and 24 (7.1%) mothers said that uses of bottle increase quantity of breast milk secretion. The 258 (75.8%) mothers said that exclusive breast feeding (EBF) should be continued up to 6 months. Conclusions: Majority of mother have knowledge of early initiation of BF, colostrum, position of BF. Majority of mother have knowledge of expression of BF but less number of mother have idea about technique of expression and storage and less number of mother believe in pre lacteal feed.